1992
DOI: 10.1099/00221287-138-3-597
|View full text |Cite
|
Sign up to set email alerts
|

Transport of ferric-aerobactin into the periplasm and cytoplasm of Escherichia coli K12: role of envelope-associated proteins and effect of endogenous siderophores

Abstract: Purified (14Claerobactin, supplied exogenously to non-growing bacteria, was translocated via the periplasm into the cytoplasm of Escherichia coli K12 strains expressing the aerobactin receptor protein IutA. No significant uptake was observed into either compartment of strains lacking the iutA gene or specifically defective in tonB. Uptake into both compartments was markedly reduced, but not abolished, in an exb mutant. Accumulation of [ 4C]aerobactin in the periplasm offiuD,fiuB orfiuC mutant strains was not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The available evidence indicates that Cbl is actively transported across the outer membrane and that the TonB protein functions in energy transduction, coupling outer membrane transport to the consumption of the respiratory proton gradient across the inner membrane. It is reasonable to conclude that the TonB-dependent transport systems for the ferric siderophores are also outer membrane pumps, a conclusion that is supported by the demonstration by Wooldridge et al (26) that ferric aerobactin is actively transported across the outer membrane of E. coli. On the other hand, a recent report by Rutz et al (20) has suggested that the TonB-dependent transport systems are gated channels, which implies facilitated diffusion, but it should be noted that their results with FepA do not, in fact, rule out active transport as the mechanism of outer membrane transport of ferric enterobactin.…”
Section: Discussionmentioning
confidence: 76%
“…The available evidence indicates that Cbl is actively transported across the outer membrane and that the TonB protein functions in energy transduction, coupling outer membrane transport to the consumption of the respiratory proton gradient across the inner membrane. It is reasonable to conclude that the TonB-dependent transport systems for the ferric siderophores are also outer membrane pumps, a conclusion that is supported by the demonstration by Wooldridge et al (26) that ferric aerobactin is actively transported across the outer membrane of E. coli. On the other hand, a recent report by Rutz et al (20) has suggested that the TonB-dependent transport systems are gated channels, which implies facilitated diffusion, but it should be noted that their results with FepA do not, in fact, rule out active transport as the mechanism of outer membrane transport of ferric enterobactin.…”
Section: Discussionmentioning
confidence: 76%
“…In E. coli, the energy transduction process requires direct contact between TonB and OM receptors. This in turn leads to translocation of the associated ferri-siderophore to the periplasm and de-energisation of TonB [32,33]. Substitutions in this region inactivate the transport capability of the corresponding receptor, but such e¡ects can be reversed by complementary substitutions in TonB suggesting that the TonB box region, thought to be located in the periplasm, physically interacts with the TonB protein.…”
Section: The Tonb-exbb-exbd Complexmentioning
confidence: 99%
“…It is believed that ExbB and ExbD use the mem- brane electro-chemical charge gradient to produce an 'energised' form of TonB that mediates a conformational change in the liganded OM receptor. This in turn leads to translocation of the associated ferri-siderophore to the periplasm and de-energisation of TonB [32,33]. The deenergised form of TonB then 'recycles' back to the CM [34,35].…”
Section: The Tonb-exbb-exbd Complexmentioning
confidence: 99%
“…This might allow TonB to contact specific regions on the receptor. It appears that "energized" TonB is then able to deliver its energy to the receptor, resulting in ligand translocation into the periplasm (10,11). ExbB⅐ExbD are implicated in the recycling of TonB, from its high affinity OM receptor association to a high affinity inner membrane association (12,13).…”
mentioning
confidence: 99%